Analysis Of The Development Of Online Loans And Gen Z Income In Indonesia In The Era Of The Industrial Revolution 4.0 - Debby Cyntia Asmah; Prawidya Hariani Rs (Proceeding International Seminar of Islamic Studies, 2019)
The unrest and complaints against fintech or PM-Fintech have recently been very lively on social media, for example on Twitter, Instagram, and Facebook. There are many netizens who report the presence of callers from various fintech companies to the list of contact numbers. So that this study has the aim of conducting a descriptive economic analysis of legal and illegal online loan institutions from 2017-2021, conducting a descriptive economic analysis of the development of crime that occurs due to illegal loans in Indonesia in 2020-2021, analyzing factors that affect GEN Z making online loans. The methods used in this study are quantitative and quality research or commonly referred to as the Mix Method. The result of this research is that the development of online loan companies is increasing every year but for those registered with the ojk is decreasing, the development of Online Loan Crime is increasing rapidly, this is seen from the many complaints to the OJK and the news circulating, lifestyle factors do not have an effect and are significant on Online Loans, the Needs Factor has a positive and significant effect on Online Loans,  Access to Financial Institutions has a positive and significant effect on Online Loans.